Calli-VA: A Visual Analytics System for Analyzing and Comparing Chinese Calligraphic Styles - Li, Jincheng; Wu, Jinpeng; Tan, Shaocong; Du, Lin; Zhang, Yu; Yang, Chaofan; Zhang, Jiadi; Xu, Rebecca Ruige; Shi, Rui; Bai, Lu; Yuan, Xiaoru (IEEE transactions on visualization and computer graphics, 2025)
Chinese calligraphy is a quintessential element of Chinese cultural heritage. Analyzing and comparing calligraphic styles not only enhances the appreciation, learning, and advancement of calligraphy but also provides valuable insights into ancient China. However, such analysis remains challenging due to the limited scalability and possible inconsistencies of qualitative methods, as well as usability and misalignment issues in conventional quantitative approaches. We propose Calli-VA, a visual analytics system, to address these challenges. Calli-VA extracts character images and their corresponding strokes from original works and characterizes each character using systematic criteria. During analysis, the system defines the analysis scope by overview and uncovers relationships between characters. Explanation and recommendation mechanisms are integrated to help users understand patterns and guide further exploration. A documentation feature allows users to record and share their findings. We demonstrate the effectiveness of Calli-VA through three case studies and expert feedback.